The world's search for sustainable development : a perspective from the global south - Sanwal, Mukul
"This book presents an authentic and sophisticated voice of the developing world on a theme of global significance. Given the fact that the fate of efforts to address the challenge of sustainable development will lie in the actions of countries like China, India and Indonesia, coming to terms with this call for reframing and will be a necessary condition for success in addressing the challenge of sustainable development going forward."
Includes bibliographical references and index.
Keywords: Sustainable development; Sustainable development; Climatic changes; Climatic changes; IAS as an author